Photochemistry and Vibrational Spectroscopy of the Trans and Cis Conformers of Acetic Acid in Solid Argon - Maçôas, E. M. S. (2004)
Acetic acid monomer has two stable geometries, the cis and trans conformers. The high-energy cis conformer has been recently detected experimentally for the first time [Maçôas et al. J. Am. Chem. Soc. 2003, 125, 16188]. The cis conformer can be produced in low-temperature rare-gas matrixes upon vibrational excitation of the ground-state trans conformer. Fast tunneling from cis- to trans-acetic acid takes place even at the lowest working temperatures (8 K), limiting the time available to study the high-energy form. Deuteration of the hydroxyl group reduces the tunneling rate by approximately 4 orders of magnitude, increasing accordingly the lifetime of the unstable conformer and its available concentration. In this work, we present a detailed analysis of the vibrational spectra of the cis form of four acetic acid isotopologues (CH3COOH, CH3COOD, CD3COOH and CD3COOD). Photolysis (193 nm) of the trans and cis forms of the perdeuterated compound was performed to evaluate the possible conformational dependence of photodissociation of acetic acid. However, no evidence of conformer specific photodissociation was found. The UV photolysis of the matrix-isolated acetic acid reveals very different products from the gas phase. Methanol complexed with carbon monoxide is the major product of photolysis of acetic acid isolated in Ar matrixes whereas it has never been observed as a photolysis product in the gas phase.